113k views
4 votes
Which expression is equivalent -6(-2/3+2x0

1. -4-12x
2. -4+2x
3. 4-12x
4. 4+12x

User Kyuuhachi
by
5.6k points

2 Answers

4 votes

Answer:

Number 3

Explanation:

-6(
(-2)/(3) + 2x) [distribute -6 to
(-2)/(3) and 2x]

= (-6 ×
(-2)/(3)) + (-6 × 2x)

= (-6 ×
(-1)/(3) × 2) + (-12x)

= (2 × 2) - 12x

= 4 - 12x

User Cyonder
by
4.9k points
2 votes

Answer:

3

Explanation:

User Driangle
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.